Оцінка внеску науково-технологічного прогресу в економічне зростання промислових регіонів України - Kharazishvili, Yuri M. (Institute of Industrial Economics of NAS of Ukraine, 2018)
The study of economic growth models based on the Cobb-Douglas production functions was carried out to determine the contribution of advancement of science and technology (AST) as aggregate factor productivity and the result of innovation activity to the economic growth. Thedefects of production functions are revealed in the statistical identification of parameters, which leads to distorted estimates. Therefore, one can not use these functions in order to determine the AST as a "the Solow residual" because of the possible approximation of statistical error of the required value of AST.To determine the rates of the AST as the “the Solow residual” in case for industrial regions and types of economic activity, the model of the aggregate supply function based on the modified by author Cobb-Douglas function is applied in the paper. In doing that, such mentioned inaccuracies has been taking into account by: using of the production output instead of GDP on the left side of the function; using of labour inputs instead of the number of employees; taking into consideration also the other category of employees, brought to the equivalent of employees with all taxes and wages; indexing of fixed assets on the GDP deflator and the impact of investments and consumption of fixed capital; analytical determining of the coefficient of capital charge; dynamic determining of elasticity coefficients.An approach is proposed in which the identification of the production function is carried out by analytical methods for each individual period and does not require the presence of long time series of variables. This approach allows to precisely reflect the production output or GDP and provides a causal link between input and output data, as well as allows to define the AST as the “the Solow residual”. The universality of the aggregate supply function`s model makes it possible to determine the contribution of the AST to the economic growth both at the country level and at the level of regions and types of economic activity. However, the applicability of the approach to assessing the contribution of the AST as the “the Solow residual” to the economic growth is limited to past periods and can be used as comparative values to determine the dependence of the endogenous prediction of future changes to AST that are dependent on diverse investments.The results of the calculations revealed that over the past 17 years, the contribution of the AST to the economic growth in the industrial regions of Ukraine was negative, that is, it reduced the return on macrofactors by an average of 3-4% a year. The situation is due to the fact that all factors of production do not receive a proper impetus for development in the face of progressing corruption and the shadow economy. Therefore, one should not expect positive growth rates of the AST, and hence the economic growth in Ukraine. In fact, there is a scientific and technological regression with the immediate prospect of the country's economy destruction. The main measures for changing economic and social policy are proposed.